A balancing domain decomposition by constraints preconditioner for a weakly over‐penalized symmetric interior penalty method. Issue 3 (29th March 2012) - Brenner, Susanne C.; Park, Eun‐Hee; Sung, Li‐Yeng
SUMMARY We develop a balancing domain decomposition by constraints preconditioner for a weakly over‐penalized symmetric interior penalty method for second‐order elliptic problems. We show that the condition number of the preconditioned system satisfies similar estimates as those for conforming finite element methods. Corroborating numerical results are also presented. Copyright © 2012 John Wiley & Sons, Ltd.